Analysis of E-Democracy in the Simultaneous General Election - Herawati Nurjamilah; Ike Rachmawati; Yana Fajar FY Basori (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This study aims to determine the development of e-democracy in the 2019 simultaneous general elections in Sukabumi City, which is supported by the high number of internet users in Sukabumi City. To measure e-democracy, researchers adopted the e-democracy model developed by Caldow (2004), which consists of 4 quadrants. The method used in this research is a quantitative method with a descriptive approach. Data collection techniques in this study were by distributing questionnaires, observations, interviews and literature studies. The population in this study were all people of Sukabumi City who were registered as the Permanent Voters List (DPT) in the Sukabumi City area, with a total of 100 respondents from 7 sub-districts in Sukabumi City. The sampling technique used by researchers was probability sampling with cluster sampling technique. Data processing in this study used Statistical Product and Service Solutions (SPSS) 26. The result of this study is that e-democracy activities in Sukabumi City are in the high category, where based on the hypothesis test, obtained ttabel 1.660 < tcount 10.127, then H0 is rejected, and Ha is accepted. The accepted hypothesis reads that the level of e-democracy in the 2019 simultaneous general elections in Sukabumi City is above 50%.